Editorial - Thorsen, Liv Emma (Tidsskrift for kulturforskning, 2010)
How has nature been put on display in different rooms and by different means - in museums, in private homes, by visual technologies or in textbooks? This was the point of departure for a seminar arranged by the project "Nature and the Natural" in Oslo 24. October 2008. This issue of Tidsskrift for kulturforskning presents three of the papers given at the seminar. These articles elucidate museum displays of nature and nature transferred to the private home. The other two discuss respectively the display of nature in zoos and the display of nature as a text.